Berberine as a potential agent for breast cancer therapy - Zhong, Xiao-Dan; Chen, Li-Juan; Xu, Xin-Yang; Liu, Yan-Jun; Tao, Fan; Zhu, Ming-Hui; Li, Chang-Yun; Zhao, Dan; Yang, Guan-Jun; Chen, Jiong (Frontiers in Oncology, 2022)
Breast cancer (BC) is a common malignancy mainly occurred in the female and it has become the most diagnosed cancer annually since 2020. Berberine (BBR), an alkaloid extracted from the Berberidacea family, has been found with broad pharmacological bioactivities including anti-inflammatory, anti-diabetic, anti-hypertensive, anti-obesity, antidepressant, and anti-cancer effects. Mounting evidence shows that BBR is a safe and effective agent with good anticancer activity against BC. However, its detailed underlying mechanism in BC treatment remains unclear. Herein, we will provide the evidence for BBR in BC therapy and summarize its potential mechanisms. This review briefly introduces the source，metabolism, and biological function of BBR, and emphasizes the therapeutic effects of BBR against BC via directly interacting with effector proteins, transcriptional regulatory elements, miRNA, and several BBR-mediated signaling pathways. Moreover, the novel BBR-based therapeutic strategies against BC improve the biocompatibility, water solubility and efficacies of BBR are also briefly discussed. Finally, the status of BBR in BC treatment and future research directions are also prospected.